An Analysis of Code Mixing in A Presentation in Tenth Grade of Vocational School at SMK Agribisnis DangauDatuk Bengkulu - Mentari, Lidya Rona (Journal of English for Specific Purposes in Indonesia, 2022)
This study looked at the many sorts of code-mixing in the tenth grade at SMK Agribisnis Dangau Datuk Bengkulu. Suwito's theories were utilized in this study. Because the researcher wanted to study verbal in the tenth grade of SMK Agribisnis Dangau Datuk Bengkulu, the researcher employed a descriptive qualitative method. Students' utterances in presentation at SMK Agribisnis Dangau Datuk Bengkulu wereused as a source of data in this study. The results of this research are 50% of word insertion, 25% of phrase, 4,17% hybrid, 4,17% of idiom, 4,17% of repetition=4,17%, and 12,5% of clause. The most used type of translation is word insertion, followedby a clause.